The regular application of fresh pig manure for milkfish culture in brackishwater ponds - Tamse, Armando P. (Iloilo City University of the Philippines in the Visayas, 1983)
The effects of regular broadcasting of fresh pig manure in brackishwater milkfish pond were studied. two treatments (unfertilized control and manured), replicated four times and assigned in a completely randomized design, were conducted in eight 100 m2 earthen ponds of the Brackishwater Aquaculture Center, Leganes, Iloilo, Philippines. Safe maximum daily manuring dosage was determined in micropond (plastic enclosures set in a pond) experiments with laboratory BOD1 and total solids of the manure as guide. BOD1 was measured at three temperature regimes (25 o, 30 o, and 35-37 C) and three salinity levels (15, 30 and 45 ppt), and three levels of dry matter content of manure (26, 32, and 36%). The BOD1 of manure intensified salinity up to 30 ppt (but inhibited at higher salinity), and with increasing dry matter content. The dry matter (X = 28%) and other physical characteristics of pig manure during a one-year period was relatively uniform. Calculated manuring dosage based on BOD1 did not reduce early morning oxygen saturation in microponds. Addition of higher amount of manure (0.01 g organic matter /1 to 2.12 g/1) in microponds indicated that 0.01 g/1 reduced next day's early morning oxygen saturation by 20% (1mg 02/1). Its use in calculatingmanure dosage for regular manuring of milkfish ponds showed varying oxygen saturation response which seemed to be correlated with the manuring dosage in g fresh wt/1 of pond water and the number of days of application due to residual effect of previous loading. Multiple regression analysis generated this equation which was significant at the 10% level (n = 76) 02 Saturation = 24.65 reduction + (176.56 + 158) manuring dosage + (0.2 + 0.1) number of days. Regular manuring effected higher fish production (285.6 kg/ha in 70 days) than in controls (183.5 kg/ha), with milkfish survival of 97.5% and 100%, respectively. Manured ponds had higher phosphorus levels (in water) and gross primary productivity values. However, exposure to longer diurnal pulse of low oxygen saturation may have affected growth rate (0.89 g/day), aside from other environmental factors. Inherent pond characteristics influenced manuring effect. Ponds with slightly acidic water reduced phosphorus levels in water which lead to relatively lower primary productivity values. The same ponds also had erratic morning oxygen saturation with values ranging from very low (12%) to quite high (120%).
Thesis (M.S. in Fisheries-Aquaculture) : CFOS, University of the Philippines in the Visayas, February 1983.